PENGARUH EXPERIENTIAL MARKETING DAN SERVICESCAPE TERHADAP CUSTOMER SATISFACTION DAN REPURCHASE INTENTION PADA SUAR COFFEE HQ PEKANBARU - ,Rendra Wasnury, Rizki Rijalul Afkar ,Sri Restuti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Currently, both as a traded good and as a beverage to be consumed, coffee has gained popularity among Indonesians. In addition to coffee, the location where it is sold, or the coffee shop, is also noteworthy. These days, both as a place to drink coffee and as a place to hang out, coffee and coffee shops have become popular. This means that a coffee shop's value is now determined not only by the caliber of the coffee it serves, but also by the extent to which the owner is able to engage and engage the senses of the customer through a pleasant environment, feelings, and service. Experiential marketing refers to experiences that appeal to the senses. While the Servicescape refers to the physical environment, which includes services for both interior and exterior facilities. This will be able to manipulate consumer behavior to feel comfortable and satisfied by giving customers a satisfying experience through service and pampering them in a nice physical environment. Feelings of customer satisfaction will encourage them to return and make additional purchases. 130 Pekanbaru City citizens were used in this study as respondents. According to the study's findings, Customer Satisfaction and Intention to Repurchase are positively and significantly impacted by the Experiential Marketing and Servicescape variables. The factor that has the biggest impact on both customer satisfaction and repurchase intention is experiential marketing. Keyword: Experiential Marketing, Servicescape, Customer Satisfaction, Repurchase Intention, Consumer Behavior